Does the Discourse on the Increase of Value Added Tax Have any legitimacy? Utilitarian Point of View - M. Aufar Saputra Pratama Erawan; Zaid Zaid; Muhammad Oky Fauzi (Universitas Pendidikan Ganesha, 2021)
Recently, Indonesia has introduced and planned a tax imposition program, which was announced through the planned imposition of Value Added Tax (PPN) on Nine Basic Ingredients (sembako). Not only that, it turns out that the Government of Indonesia will also impose taxes on other services, such as; Education and Orphanages and Orphanages. As a result, there is a potential for rebellion resulting from some of these plans. This study aims to examine and examine the fifth KUP Bill, which increases tariffs and the imposition of VAT on goods and services that should be excluded. This type of research is normative legal research. This study uses a law application approach and a conceptual approach. The primary sources used are secondary data sources (library materials). The analytical technique used is a descriptive, prescriptive analysis technique, which is specifically given to provide arguments for the results of research that has been carried out. This study found that the VAT rate will reach 12% with a minimum of 5% and a maximum of 15%. Moreover, in general, this policy can violate the principle of utilitarianism because it will harm social welfare. However, if VAT is only imposed on certain goods and services that are more exclusive to subsidize goods and services consumed by the poor, it will gain legitimacy in utilitarianism.